Epic negation : the dialectical poetics of late modernism - Blanton, C. D. (Charles Daniel), 1968- (Oxford University Press, 2015)
"Epic Negation examines the dialectical turn of modernist poetry over the interwar period, arguing that late modernism inverts the method of Ezra Pound's "poem including history" to conceive a negated mode of epic, predicated on the encryption of disarticulated historical content. Compelled to register the force of a totality it cannot represent, this negated epic reorients the function of poetic language and reference, remaking the poem, and late modernism generally, as a critical instrument of dialectical reason. Part I reads The Waste Land alongside the review it prefaced, The Criterion, arguing that the poem establishes the editorial method with which T.S. Eliot constructs the review's totalizing account of culture. Dividing the epic's critical function from its style, Eliot not only includes history differently, but also formulates an intricately dialectical account of the interwar crisis of bourgeois culture, formed in the image of a Marxian critique it opposes. Part II turns to the second war's onset, tracing the dislocated formal effects of an epic gone underground. In the elegies and pastorals of W.H. Auden and Louis MacNeice, lyric forms divulge the determining force of unmentionable but universal events, dividing experience against consciousness. With H.D.'s war trilogy, produced in a terse exchange with Freud's Moses, even the poetic image lapses, associating epic with the silent historical force of the unconscious as such"-- Provided by publisher
Keywords: American poetry -- 20th century -- History and criticism -- Theory, etc.; English poetry -- 20th century -- History and criticism -- Theory, etc.; Modernism (Literature); Poetry -- Explication.; Epic poetry, American -- History and criticism.; Epic poetry, English -- History and criticism.; Poetry, Modern -- 20th century -- History and criticism.; Poetics.; Literature -- Philosophy.; Poésie américaine -- 20e siècle -- Histoire et critique -- Théorie, etc.; Poésie anglaise -- 20e siècle -- Histoire et critique -- Théorie, etc.; Modernisme (Littérature); Poésie -- Explication de texte.; Poésie épique américaine -- Histoire et critique.; Poésie épique anglaise -- Histoire et critique.; Poétique.; LITERARY CRITICISM -- Poetry.; Literature -- Philosophy; Epic poetry, American; Epic poetry, English; Poetics; Poetry -- Explication; Poetry, Modern; 1900-1999; Electronic books.; Criticism, interpretation, etc.